2020
DOI: 10.3390/genes11111329
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Spectrum of Syndromic and Non-Syndromic Hearing Loss in Pakistani Families

Abstract: The current molecular genetic diagnostic rates for hereditary hearing loss (HL) vary considerably according to the population background. Pakistan and other countries with high rates of consanguineous marriages have served as a unique resource for studying rare and novel forms of recessive HL. A combined exome sequencing, bioinformatics analysis, and gene mapping approach for 21 consanguineous Pakistani families revealed 13 pathogenic or likely pathogenic variants in the genes GJB2, MYO7A, FGF3, CDC14A, SLITRK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 63 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…The majority of MYO15A variants have been related to congenital or postlingual deafness (Zhang et al, 2019). They are frequently found in consanguineous families in Mideast countries (Doll et al, 2020;Noman et al, 2019;…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of MYO15A variants have been related to congenital or postlingual deafness (Zhang et al, 2019). They are frequently found in consanguineous families in Mideast countries (Doll et al, 2020;Noman et al, 2019;…”
Section: Discussionmentioning
confidence: 99%
“…The majority of MYO15A variants have been related to congenital or postlingual deafness (Zhang et al, 2019). They are frequently found in consanguineous families in Mideast countries (Doll et al, 2020; Noman et al, 2019; Shafique et al, 2014). In contrary, genetic impact of MYO15A was less reported in China (Wang et al, 2020; Zhang et al, 2019), where nonconsanguineous marriage is predominant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic testing for etiologic evaluation has become a standard of care in people with congenital or childhood-onset sensorineural HL, which is caused by pathologies of the inner ear and auditory nerve ( 4 , 5 ). Recent studies have shown that screening all recognized HL genes for variants reveals underlying cause in about half of the affected individuals, leaving a significant portion of people with HL with an unknown etiology ( 6 9 ). In the era of emerging genetic therapies for HL, finding the etiology of HL in affected individuals has become a critical task.…”
mentioning
confidence: 99%
“…In both studies, GJB2 and STRC were the most frequently mutated genes among the recessive cases, and MYO6 among the dominant ones. Finally, in the third broad epidemiological study in this Special Issue, Doll et al investigated 21 Pakistani consanguineous families with autosomal recessive HI [16]. The cohort included 5 syndromic and 16 non-syndromic cases.…”
mentioning
confidence: 99%